Exploring sulphate resistance of coal mining waste blended cements through experiments and thermodynamic modelling. (August 2021) - Caneda-Martínez, Laura; Kunther, Wolfgang; Medina, César; Sánchez de Rojas, María Isabel; Frías, Moisés
Abstract: This study evaluates the sulphate resistance of blended cement derived from the addition of thermally activated coal waste as pozzolan, at replacement levels of 0%, 20% (CMW20) and 50% (CMW50) with a multi-method approach. The pastes were prepared at a w/b ratio of 0.5, using a water-reducing admixture in the blended pastes to compensate for their high water demand. Sulphate resistance is reduced in CMW20 pastes, while long-term benefits are observed for CMW50 pastes, although moderate signs of deterioration are observed at the beginning of the exposure. The initial damage in CMW50 pastes is attributable to the precipitation of products (mainly ettringite and monosulphoaluminate) in the small capillary pores (<0.01 μm). This is prevented in OPC and CMW20 pastes since their microstructure allow the precipitation in the macropores (>0.05 μm). The greater long-term resistance of CMW50 pastes was explained by thermodynamic calculations, which suggests that the lower calcium leachability of these cements prevented gypsum formation. This, together with the higher content of carboaluminate phases, leads to lower supersaturation levels in the pore solution with respect to ettringite, reducing stresses derived from sulphate exposure.